Mental Health During COVID-19: Tam Giao and Vietnam's Response - Small, Sean; Blanc, Judite (Frontiers in Psychiatry, 2021)
COVID-19 is a novel infectious disease and global health crisis with major psychological implications. Of particular focus are the effects it will have on low- and middle-income countries (LMICs) as being under-resourced poses many challenges. Vietnam, a country with an estimated population of 97.33 million people, which until 30 July, 2020, had 459 confirmed COVID-19 cases with no fatalities but as of November 4th had 35 deaths, can be viewed as a model LMIC for other countries struggling with COVID-19.28 Employing key tactics such as transparency and effective communication, Vietnam was able to foster strong cooperation between government and citizens, contributing to its success during COVID-19. Moreover, Vietnamese resilience, attributable, in part, to “tam giao”, a coexistence of religious and philosophical Taoism, Buddhism, and Confucianism through cultural additivity, provides a unique mindset that other countries can learn from to adapt and even build psychological resilience against COVID-19 pandemic’s psychological outcomes. We suggest countries prioritize transparency and communication to mitigate stigmatization and psychological distress that can result from quarantine and other interventions while promoting resources that provide accurate scientific information and psychological aid to citizens. We believe that Tam giao could be repurposed to relieve inevitable contradictions between values and lifestyles in the context of this devastating global health crisis.